Lactation performance of purebred Arsi and Friesian X Arsi crosses under prepartum and postpartum supplementary feeding regimes in Ethiopia - Tawah, C.L.; Mohammed-Kurtu, Y.; Rege, J.E.O.; Alemayehu, N.; Shibre, M. (Ethiopian Society of Animal Production, 1995)
A study was conducted at the Asella Station in the Arsi Region of Ethiopia to investigate the dairy performance of purebred indigenous Arsi and Friesian x Arsi crosses under different pre- and post-partum supplementary feeding regimes. Lactational performance of both genotypes was not affected by prepartum supplementation. Postpartum supplementation significantly affected milk yield and butterfat percent of Arsi crosses. Arsi crosses produced more milk over a longer lactation period, but with a less proportion of butterfat in milk than purebred Arsi. Purebred Arsi showed considerably more variation in milk yield, lactation length and butterfat percent than Arsi crosses. First-crosses produced slightly more milk over a shorter lactation period and proportionally more butterfat in milk than backcrosses. It was observed that there is little benefit from pre-partum supplementation in terms of milk production. However, the conventional wisdom that prepartum supplementation might be beneficial for the viability of calves and for cow reproduction should be investigated.